THE EFFECT OF FIELD TRIP METHOD IN WRITING DESCRIPTIVE TEXT BY 11 GRADE STUDENTS OF SMA NEGERI 1 KUTACANE ACADEMIC YEAR 2022/2023 - Firman Anugrah; Raja Fauziah; Wikiaprian Pinim (STKIP USMAN SAFRI KUTACANE, 2025)
The aims of this research are to know: 1) the application of field trip method in teaching writing descriptive text 2) the students’ writing descriptive text effect before and after using field trip method 3) Whether there is a significant effect of field trip method on students’ writing descriptive text effect at the eleven grade of SMA Negeri 1 Kutacane. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research is all of the eleven grade students’ of SMA Negeri 1 Kutacane which consist of 212 students. Sample are XI IPA core 2 which consist of 34 students which taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The results of this research are: 1) the effect of field trip method is 3.8, it is categorized “very good” 2) the mean score of students writing descriptive text effect is 55 it is categorized “fail”. Meanwhile, after using field trip method is 76,91 it is categorized “good”. 3) There is a significant effect of using field trip method on students’ writing descriptive text effect at the eleven grade of SMA Negeri 1 Kutacane. The result of data analysis shows that ttest is higher than ttable (ttest25.18 > ttable2.52). So, the hypothesis is accepted. It means that, there is a significant effect of field trip method on students’ writing descriptive text effect at the eleven grade of SMA Negeri 1 Kutacane in 2022/2023 Academic Year.